Research on pricing strategy of shared electro-thermal-hydrogen energy storage in integrated energy multi-microgrid based on hybrid game - Zhou, Huan; Wei, Jie (Frontiers in Energy Research, 2025)
Against the backdrop of high investment costs in distributed energy storage systems, this paper proposes a bi-level energy management model based on shared multi-type energy storage to enhance system economics and resource utilization efficiency. First, an electricity–heat–hydrogen coupled shared storage architecture is developed, incorporating hydrogen-blended gas turbines, gas boilers, and hydrogen loads to achieve deep coupling between the power grid and natural gas network. Then, a bi-level game model is formulated with the upper-level objective of minimizing the storage operator’s cost and the lower-level objective of minimizing the cost of the integrated energy microgrid (IEM) aggregator. A cooperative game mechanism is introduced within the microgrids to support peer-to-peer energy trading. Nash bargaining theory is applied to determine benefit allocation and dynamic pricing strategies among microgrids. The model is solved using a genetic algorithm (GA) and the alternating direction method of multipliers (ADMM). Simulation results validate the proposed strategy’s effectiveness and feasibility in reducing system costs, improving overall benefits, and achieving fair benefit allocation.